Application of phase change cold storage technology in the low carbon transition of cold chain transportion - ZHU Aochang; LI Chuanchang* (能源环境保护)
The high energy consumption and high emissions of traditional cold chain transportation are considered to be a major challenge to achieving ′carbon peaking′ and ′carbon neutrality′ in the logistics and transportation industry. As an emerging technology developed in recent years, phase change cold storage technology is expected to greatly reduce refrigeration load, energy consumption, and greenhouse gas emissions. This paper compares the carbon footprint of traditional cold chain transportation with that of cold chain transportation loaded with phase change cold storage technology, clarifies the application potential of phase change cold storage technology in the low carbon transformation of cold chain transportation, and analyzes the cold storage technology requirements for different types of cold chain transportation. The key of phase change cold storage technology is the performance regulation of phase change cold storage materials and encapsulation technology. The performance regulation focuses on adjusting the phase change temperature to meet the cold storage requirements of different cargoes, while the encapsulation technology focuses on solving the leakage problem of phase change materials and enhancing their thermal conductivity. Phase change cold storage technology and cold chain transport integration in a variety of ways, can: with the combination of refrigerated vehicle enclosure structure; made of eutectic plate placed inside the box, and traditional refrigeration unit integration or made of passive cooling cold chain transport box. The focus of future research on phase change cold chain transport is to develop high-performance phase change cold storage materials and to realize multi-temperature control and intelligence of the cold chain transport process.